The gods rich in praise : early Greek and Mesopotamian religious poetry - Metcalf, Christopher (Oxford classical monographs, 2015)
This title contributes to the current academic debate on the relationship between early Greek poetry and the ancient Near East, especially Mesopotamia. It is the first extensive study to be based on a detailed analysis of the ancient texts, consisting in this case of a selection of religious poems mainly in Sumerian, Akkadian, Hittite, and Greek